Indonesia Response and Recent Development of Law and Policy in Addressing Marine Plastic Litter - Maruf, Maruf (Faculty of Law, Universitas Negeri Semarang, 2019)
Marine plastic litter is one of the major problems that undermine the Indonesian Government’s vision for making the sea as the future for the Indonesian nation. Marine areas of Indonesia are endangered by the massive plastic pollution, which is causing serious marine environmental problems. Indonesia is referred to as the biggest source of plastic waste in Southeast Asia and second biggest in the world. Indonesia government through Presidential Decree No. 7/2017 has established National Plan of Action (NPOA) on Marine Plastic Debris Management to strengthen the Indonesian commitment in reducing marine plastic litter. Furthermore, the Indonesian government also enacted Presidential Regulation No. 83/2018 on Handling Marine Litter. Thus, the present study argues that it is of paramount necessity to assess the impact of the legal framework regulating marine plastic litter in Indonesia in order to identify the lacuna in the existing legislative and policy framework for dealing with marine environmental pollution caused by marine plastic litter.